Distributional Fate of Elements during the Synthesis of Zeolites from South African Coal Fly Ash - Du Plessis, Pieter W. (Materials (Basel), 2014)
The synthesis of zeolites from South African coal fly ash has been deemed a viable solution to the growing economical strain caused by the disposal of ash in the country. Two synthesis routes have been studied thus far namely the 2-step method and the fusion assisted process. Fly ash contains several elements originating from coal which is incorporated in the ash during combustion. It is vital to determine the final destination of these elements in order to unveil optimization opportunities for scale-up purposes. The aim of this study was to perform a material balance study on both synthesis routes to determine the distributional fate of these elements during the synthesis of zeolites. Zeolites were first synthesized by means of the two synthesis routes. The composition of all raw materials and products were determined after which an overall and elemental balance were performed. Results indicated that in the 2-step method almost all elements were concentrated in the solid zeolite product while during the fusion assisted route the elements mostly report to the solid waste. Toxic elements such as Pb, Hg, Al, As and Nb were found in both the supernatant waste and washing water resulting from each synthesis route. It has also been seen that large quantities of Si and Al are wasted in the supernatant waste. It is highly recommended that the opportunity to recycle this liquid waste be investigated for scale-up purposes. Results also indicate that efficiency whereby Si and Al are extracted from fused ash is exceptionally poor and should be optimized.